Effect of Fe3O4 Nanoparticles on Mixed POPC/DPPC Monolayers at Air-Water Interface. (3rd March 2019) - Xu, Zhuangwei; Hao, Changchun; Xie, Bin; Sun, Runguang
Abstract : Fe3 O4 nanoparticles (NPs) as a commonly used carrier in targeted drug delivery are widely used to carry drugs for the treatment of diseases. However, the mechanism of action of between Fe3 O4 NPs and biological membranes is still unclear. Therefore, this article reports the influence of hydrophilic and hydrophobic Fe3 O4 NPs on mixed 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC) and 1, 2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) that were studied using the Langmuir-Blodgett (LB) film technique and an atomic force microscope (AFM). From surface pressure-area (π -A ) isotherms, we have calculated the compression modulus. The results showed that hydrophobic Fe3 O4 NPs enlarged the liquid-expanded (LE) and liquid-condensed (LC) phase of the mixed POPC/DPPC monolayers. The compressibility modulus of the mixed POPC/DPPC monolayer increases for hydrophilic Fe3 O4 NPs, but the opposite happens for the hydrophobic Fe3 O4 NPs. The adsorption of hydrophobic Fe3 O4 NPs in mixed POPC/DPPC monolayers was much more than the hydrophilic Fe3 O4 NPs. The interaction of hydrophilic Fe3 O4 NPs with the head polar group of the mixed lipids increased the attraction force among the molecules, while the interaction of hydrophobic Fe3 O4 NPs with the tail chain of the mixed lipids enhanced the repulsive force. The morphology of the monolayers was observed by AFM for validating the inferred results. This study is of great help for the application of Fe3 O4 NPs in biological systems.